EMPOWERING OF DISABLED ENTREPRENEURS THROUGH MAXIMIZATION BENEFIT OF SMALL BUSINESS LOAN - Wening Estiningsih (JABE (Journal of Applied Business and Economic), 2014)
Disabled  communities  is one of the  marginalized  communities  in the development process and policies,  it also happens to disabled  entrepreneurs.  In the concept of empowerment, disabled entrepreneurs should be given  the ease  in obtaining a small business loan. This study is a conceptual paper, secondary data sourced  from the  literature review  related to  empowerment  and  small business loans.The aims of this study is to  provide an overview  the importance of  the empowerment of disabled entrepreneurs through maximizing the benefits of small business loans  and  study  is expected to  be a reference for policy development related to the empowerment of disabled entrepreneurs.